PEMANFAATAN MEDIA APE MENGANCING BAJU DALAM PENGEMBANGAN MOTORIK HALUS ANAK USIA DINI - Asyifa Marefia; Desi Hulandari; Nanda Putri K.S; Nesya Azzahara; Resya Nabilla; Rianti Arvina; Rizky Surya Amanda; Winda Sherly Utami (STKIP Subang, 2026)
This study is motivated by the importance of developing fine motor skills in early childhood through the use of appropriate and engaging learning media. One of the media that can be used is an Educational Play Tool (APE) in the form of buttoning clothes, which helps train children's hand-eye coordination. The purpose of this study is to determine the use of buttoning APE in developing fine motor skills of early childhood in the home environment. This research uses a qualitative descriptive method with data collection techniques including observation of two children aged 5–6 years and interviews with their parents. The results show that the use of buttoning APE can improve children's fine motor skills, such as pinching, inserting buttons into holes, as well as fostering patience and independence. Children appear more interested and active in learning activities that are carried out directly and in a fun way. Therefore, buttoning APE is effective as a medium to stimulate fine motor development in early childhood within the family environment.